PECULIARITIES OF IXODID TICK-BORNE BORRELIOSIS MORBIDITY WITHIN IRKUTSK RESIDENTS DEPENDING ON GEOGRAPHICAL PLACE OF INFECTION - O. V. Melnikova; E. A. Vershinin; E. A. Sidorova; E. I. Andayev (Acta Biomedica Scientifica)
Six hundred and ninety three cases of ixodid tick-borne borreliosis in Irkutsk city residents duing17-year period. (1995-2011) have been analyzed. It was revealed that the most risk of Borrelia burgdorferi infection is for visitors of zones along Baikalsky, Goloustnensky and. Melnichny routes as well as green zones in Irkutsk from the end. of May up to the beginning of July. Individuals older than 40 years of both sexes suffer from the disease more often. Erythema is marked in more than 80 % of patients. Body is character place of the tick's bite for adults, head - in children.